Time-restricted feeding alleviates arthritis symptoms augmented by high-fat diet - Búr, Zsófia; Vendl, Bernadett; Sűdy, Ágnes R.; Lumniczky, Zalán; Szántó, Csongor G.; Mócsai, Attila; Káldi, Krisztina; Ella, Krisztina (Frontiers in Immunology, 2025)
Rheumatoid arthritis (RA) affects approximately 1% of the global population. Its hallmark symptoms include severe pain and joint stiffness, which significantly diminish life quality. RA’s development is influenced by multiple factors including unhealthy lifestyle habits. Calorie-rich diets, particularly those high in fat and resulting in obesity, are associated with RA and exacerbate its symptoms. Consequently, dietary modifications are recommended as a complementary treatment. However, adherence is often low due to the restrictive changes required in nutrient composition or caloric intake. Our previous findings indicate that time-restricted feeding (TRF) benefits leukocyte rhythm and mitigates autoimmune responses. In this study we explored the impact of TRF on the severity of K/BxN serum-transfer arthritis (STA) in mice subjected to high-fat diet. Three feeding schedules were implemented: a control (Ctrl) with constant access to standard chow, a high-fat diet group (HF) with ad libitum food access, and a high-fat TRF group (HF-TRF) with a 10-hour feeding window during the active phase. After four weeks of conditioning, STA was induced. Although macroscopic markers of inflammation did not differ between the Ctrl and HF groups, histological analysis revealed increased inflammation in HF mice, including expanded edema, pannus formation, bone erosion, elevated synovial neutrophil infiltration and serum leptin levels. Importantly, all these inflammatory markers were significantly reduced in the HF-TRF group, along with synovial IL-1β and monocyte/macrophage counts. Our results indicate that TRF can diminish the impact of a high-fat diet on STA severity, potentially serving as a preventive method and a sustainable therapeutic support for RA management.